EVALUASI PROSEDUR AUDIT DALAM RANGKA PEMENUHAN TUJUAN AUDIT ATAS PIUTANG USAHA - Rahmayanti, Andhita Yukihana; Anggraeni, Birawani Dwi (UI Scholars Hub, 2015)
This study emphasizes the fulfillness of the audit objectives with performed by evaluating the audit procedures on accounts receivable of non-public company, both related to the audit objectives of detailed balance and the audit objectives of presentation and disclosure. Auditors perform audit procedures include tests of controls and test of detailed balance on accounts receivable account, to reach audit assurances that the audit objectives have been met so that the information and figures included in the presentation and disclosure in accordance with general acceptance standard in Indonesia. This study using the descriptive method which analyzes working papers of auditors that contains the audit procedures performed by the auditor. This study show that not all the audit objectives are met because the audit procedures are not all performed by the auditor. This has significant implications for the presentation of accounts receivable in the financial statements which are not in accordance with the accounting standards. Results of this study are expected to contribute knowledge of audit science.